3D interactive mobile navigator structure and 2D map in campus environment using GPS - Mantoro, Teddy; Saharuddin, Siti Athirah; Selamat, Supiah (2009)
This paper presents a work in progress of a system to navigate user location using Global Positioning System (GPS) in campus environment that utilizes user's Personal Digital Assistant (PDA) with built-in GPS receiver. This application provides 3D atmosphere so it will be easier for the user to recognize a most likely place to the real-world environment. The user could navigate using 3D model and at the same time can switch to the 2D maps environment. The 2D map environments assist the user to look the overall of the location on campus area. The combination of 2D map and 3D view in the system can help the user to switch between them effortlessly. This user navigation application could apply the carry on movement of the user on the map